Usefulness of somatostatin receptor scintigraphy in the management of patients with Zollinger-Ellison syndrome. Groupe de Recherche et d'Etude du Syndrome de Zollinger-Ellison (GRESZE). - Cadiot, G (1997)
BACKGROUND: Management of patients with Zollinger-Ellison syndrome (ZES) depends on the presence of multiple endocrine neoplasia type 1 (MEN 1) or liver metastases, or both. Somatostatin receptor scintigraphy (SRS) detects previously unknown endocrine tumours. AIM AND METHODS: To evaluate SRS findings susceptible to modifying the management of patients with ZES-that is, relevant findings, and the specificity of these findings. The latter were defined according to our current therapeutic strategy in three subgroups of patients (sporadic, MEN 1, and liver metastases). PATIENTS: 85 consecutive patients without known extra-abdominal metastases were studied between September 1991 and March 1996. RESULTS: Relevant findings were found in 41% of 49 patients with sporadic disease but without liver metastases, in 22% of 18 patients with MEN 1 but without liver metastases, and in 17% of 18 patients with liver metastases. Follow up was available for 20 (74%) of 27 patients who had 23 relevant findings. Nineteen relevant findings (83%) were confirmed at a median of three (range 0.25-45) months of follow up; four (17%) were not confirmed at 30 (range 12-52) months (p = 0.025). Findings located in the duodenopancreatic area (90%), chest (100%), bone (100%), and liver (60%) were confirmed. Most findings for patients with MEN 1 involved the chest. CONCLUSION: SRS detects many anomalies susceptible to modifying management of patients with ZES, especially in those with sporadic disease. The specificity of hot spots located outside the liver seems very high. By contrast, the specificity of hot spots located in the liver remains to be evaluated when conventional imaging is negative.